Pengaruh Penggunaan Metode Permainan Kartu Bilangan Terhadap Motivasi Dan Hasil Belajar Siswa Materi Pecahan - Dukan Jauhari Faruq (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2019)
This study aims to determine the effect of the use of the number card playing method on student motivation and learning outcomes in fraction material in class IV SD NU 03 Nurul Huda Wuluhan Jember. The research method used was a quasi-experimental study with a total of 20 experimental and control class students. Data collection techniques are using pretest and posttest. Analysis of the data used was the T test. The results of the data analysis with the T test at the 95% confidence level showed that the learning outcomes of the experimental class students who used the number card playing method were better than students in the control class who did not use the number card playing method. From the results of the above analysis the researcher draws the conclusion that the learning outcomes of students who use the number card game method program are higher than students who do not use the number card game method. So the number card game method can be used as an alternative learning media that can increase student motivation and learning outcomes.Keywords: Game Method, Number Cards, Learning Outcomes